STRATEGI PENGEMBANGAN PRODUK UNGGULAN KHAS MERU BETIRI - Eka Nur Jannah; Luh Putu Suciati (UNEJ e-Proceeding, 2018)
The distinctive superior product of Meru Betiri is a potential product that has competitiveness and is market oriented by utilizing abundant and diverse non-timber forest products (fruit plants and medicinal plants) in the Meru Betiri National Park area. Wonoasri Village, Tempurejo Subdistrict, Jember Regency as one of the buffer villages of the Meru Betiri National Park area has several regional special products through the Joint Business Group formed by the community as banana processing into "Cripika" banana and processed medicinal plants into syrup spices "Kraton". The high potential of bananas and medicinal plants in Wonoasri Village has required a strategy to optimize agricultural products in the downstream sector and strategic planning for marketing its products. This study aims to determine the marketing strategy in order to develop superior products typical of Meru Betiri. The research method is descriptive and analytical. The sampling method is purposive sampling. Methods of data collection are observation, interviews with questionnaires and documentation. Data analysis used is evaluation of inernal and external factors, SWOT analysis and QSPM. The results of the analysis show that alternative marketing strategies are an effort to develop a distinctive superior product of Meru Betiri based on the results of QSPM analysis: priority strategic alternatives (1) strengthening sales promotion activities with the total attractiveness score of 6.20, priority strategic alternatives (2) consistency product quality and business sustainability with the total attractiveness score of 5.95, and priority strategic alternatives (3) strengthening local economic partnerships 5.76